Disease‐specific growth charts for Korean infants with Prader–Willi syndrome. (22nd October 2014) - Lee, Jieun; Isojima, Tsuyoshi; Chang, Mi Sun; Kwun, Young Hee; Huh, Rimm; Cho, Sung Yoon; Sohn, Young Bae; Jin, Dong‐Kyu
<x xml:space="preserve">Abstract</x> Patients with Prader–Willi syndrome (PWS) present with short stature and obesity. The growth pattern of children with PWS is different from that of the healthy population. Therefore, it is not appropriate to use normal growth charts to evaluate the growth status of children with PWS. We aimed to develop disease‐specific growth charts for height and weight for nongrowth hormone‐treated Korean infants with PWS aged between 0 and 36 months and to use these growth charts for the evaluation and management of infants with PWS. We conducted a retrospective review of the medical records of 122 infants with genetically confirmed PWS. Data on the patients' height and weight measurements before they underwent growth hormone treatment were recorded. Disease‐specific growth charts were generated and the 3rd, 10th, 25th, 50th, 75th, 90th, and 97th centiles were calculated using the LMS (refers to λ, μ, and σ, respectively) smoothing procedure for height and weight. The disease‐specific growth charts for Korean infants with PWS can be used when examining infants with PWS and when evaluating their growth at later stages for comparison purposes. They are also useful for monitoring growth patterns, nutritional assessments, and recording responses to growth hormone treatment. © 2014 Wiley Periodicals, Inc.